2015
DOI: 10.1038/modpathol.2015.2
|View full text |Cite
|
Sign up to set email alerts
|

Overdiagnosis of high-grade dysplasia in Barrett's esophagus: a multicenter, international study

Abstract: Numerous histological mimics of high-grade dysplasia in Barrett's esophagus predispose to overdiagnosis and potential serious mismanagement, including unnecessary esophagectomy. This study investigates the prevalence and sources of this problem. Biopsies from 485 patients diagnosed with Barrett's high-grade dysplasia were screened for a multi-institutional, international Barrett's endoscopic ablation trial. Screening included review of the original diagnostic slides and an additional protocol endoscopy with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 21 publications
0
26
1
Order By: Relevance
“…This study, carried out in real life conditions (i.e., outside formal research trials), once again highlights the problem of biopsy interpretation in BE, not limited to the identification of dysplasia. In fact, the level of discrepancy we found in our series (78%) suggests that in the daily routine, this issue may be even more worrisome than thought based on the data inferred by research trials (18-21), even though two recent studies on consistent cohorts of patients showed that only 27% of the initial diagnoses of LGD and 51% of those of high-grade dysplasia were confirmed after a second opinion by experienced pathologists (26,27). With regard to the classification of dysplasia, there are several objective reasons that make it sometimes difficult for the pathologist to provide an accurate grading: when erosion, ulcerations, or active inflammation is present, regenerating Barrett's epithelium may feature cytologic aspects resembling dysplasia (28); in addition, biopsies may be poorly oriented or have artifacts, thus limiting an accurate evaluation of dysplasia that may be present.…”
Section: Discussioncontrasting
confidence: 52%
“…This study, carried out in real life conditions (i.e., outside formal research trials), once again highlights the problem of biopsy interpretation in BE, not limited to the identification of dysplasia. In fact, the level of discrepancy we found in our series (78%) suggests that in the daily routine, this issue may be even more worrisome than thought based on the data inferred by research trials (18-21), even though two recent studies on consistent cohorts of patients showed that only 27% of the initial diagnoses of LGD and 51% of those of high-grade dysplasia were confirmed after a second opinion by experienced pathologists (26,27). With regard to the classification of dysplasia, there are several objective reasons that make it sometimes difficult for the pathologist to provide an accurate grading: when erosion, ulcerations, or active inflammation is present, regenerating Barrett's epithelium may feature cytologic aspects resembling dysplasia (28); in addition, biopsies may be poorly oriented or have artifacts, thus limiting an accurate evaluation of dysplasia that may be present.…”
Section: Discussioncontrasting
confidence: 52%
“…Although an excellent interobserver agreement for HGD has been reported among GI pathologists,13 14 one recent study demonstrated that on review of 485 HGD samples from both academic and private centres by experienced GI pathologists, up to 40% were overdiagnosed with HGD and had to be reinterpreted as LGD, IND, ND or no BO 16. In this regard, abnormal flow cytometric results may serve as objective evidence to confirm a morphological impression or suspicion of HGD.…”
Section: Discussionmentioning
confidence: 98%
“…3,9 Unfortunately, the cornerstone of surveillance programmes, dysplasia grading, suffers from significant variation in reproducibility, even among experts in gastrointestinal pathology. Pathologists in general practice were found to have even more problems with dysplasia grading in BM, 19,20 and it has been recommended that the grade of dysplasia be confirmed by an expert pathologist. 3 We previously proposed that p53 protein accumulation in biopsies from patients with BM, detected by IHC staining, is a predictor of malignant progression.…”
Section: Discussionmentioning
confidence: 99%